The prolificacy of green transformational leadership in shaping employee green behavior during times of crises in small and medium enterprises: a moderated mediation model - Zaid, Wafaa Mohammed Ahmed; Yaqub, Muhammad Zafar (Frontiers in Psychology, 2024)
Besides various other potent efforts to contain and consolidate, post-pandemic crisis management requires an adequate display of green transformational leadership. Green transformational leaders exhibit a formidable commitment to sustainability in making managerial choices and subsequently inspiring and motivating their employees to participate vigorously in the ensuing green initiatives. Such initiatives could profoundly help organizations adjust to shifting market situations, follow requirements, and preserve stakeholder trust. While making appeals to the central tenants of the transformation leadership theory, social exchange theory, and the social cognition theory, the study examines the impact of green transformational leadership on employees' green behaviors during times of crises using employees' self-esteem as a mediator and work engagement as the critical moderator. The relevant context of the study has been the small and medium enterprises of Saudi Arabia. Data from 232 SMEs employing less than 250 employees selected through convenience sampling was collected using structured questionnaires. After performing hierarchical regression modeling using SPSS 23, macro V4 model 58, and Amos 24, it has been found that green transformational leadership is positively associated with employees' green behaviors, with selfesteem and work engagement acting as significant mediating and moderating conditions, respectively. Besides, providing firsthand empirical evidence on the impact of green transformational leadership on employees' green behaviors, in unique industrial (SMEs), contextual (times of crises), and regional (Middle Eastern) settings, the study offers useful implications to the managers aspiring to enhance the sustainable performance of their firms through maturing green behaviors among their employees.